Bourdieu and interprofessional education: what's the relevance?. Issue 1 (2nd January 2018) - Bonello, Marjorie; Wright, Jon; Morris, Jane; Sadlo, Gaynor
ABSTRACT: Interprofessional education (IPE) is perceived to be one strategy to reduce professional compartmentalisation and improve collaborative practices. The unequal power relations existing between the various professions who need to collaborate for IPE remains largely unexamined and it is only in recent years that sociological theories have been employed within the interprofessional field. This paper uses selected findings from an exploratory case study into IPE conducted at the University of Malta and then examines these findings from a Bourdieusian perspective. The first part of this paper introduces the breath of theoretical perspectives employed for IPE and then goes on to provide an overview of Bourdieu's theories of social practices. The second part outlines the context of this case study and presents selected findings. The third section discusses how these findings were examined using Bourdieu's concepts helping us demystify the various ways in which health care professions worked and interacted, and how this all made sense within a wider societal context. It also highlights the relevance of taking into account Bourdieu's concepts during the development of IPE.